Navigating Market Volatility: The Role of Gold, Crude Oil, and COVID-19 on the Stock Price - Fauzi, Fitriya; Starli, Eudokimos Brian (International Journal of Finance Research, 2025)
This study aims to analyze the influence of global gold prices, crude oil prices, and daily COVID-19 cases on the Indonesian Composite Index (IHSG) before, during, and after the COVID-19 pandemic. The study consists of three independent variables: global gold prices, crude oil prices, and daily COVID-19 cases, with one dependent variable: the IHSG. The data was taken from 2018 to 2023, covering the periods before, during, and after the pandemic. The data processing is divided into four periods: before, during, and after the pandemic, up to the overall period. This paper used the Quantile Regression 0.75 and Generalized Linear Model (GLM) research methods due to the presence of extreme outliers that prevented the data from meeting normality requirements. By using Quantile Regression 0.75 and GLM, data normality can be ruled out. Both research methods showed similar significant results. Gold has a positive effect on the IHSG, and crude oil has a larger coefficient than gold. Meanwhile, COVID-19 has a significant but negative effect, with a small coefficient, suggesting that the daily number of COVID-19 cases has no impact on the IHSG. These findings have practical implications for understanding the dynamics of the IHSG, engaging the reader's interest in the study's relevance.